A new species of Pleonexes Spence Bate, 1857 (Amphipoda: Senticaudata: Ampithoidae) from the São Pedro and São Paulo Archipelago, Equatorial Atlantic, Brazil, with comments on the genus - Souza-Filho, Jesser F.; Andrade, Luiz F. (Zootaxa, 2022)
A new species of Pleonexes from the São Pedro and São Paulo Archipelago, northeastern Brazil is described. Pleonexes lowryi sp. nov. is characterized by the slender mandible palp; the gnathopod 2 with large and rounded anterodistal lobe on the basis and strongly oblique palm; the pereopods 3–4 with slightly expanded basis; the uropod 1 peduncle with short and blunt spur; and the telson with subtriangular apex and small subdistal cusp on each side. In addition, based on the literature review, we provide new combinations of some species and a key to Pleonexes species in the world.